Titin gene mutations enhance radiotherapy efficacy via modulation of tumour immune microenvironment in rectum adenocarcinoma - Hengchang Liu; Jialiang Liu; Xu Guan; Zhixun Zhao; Pu Cheng; Haipeng Chen; Zheng Jiang; Xishan Wang (Clinical and Translational Medicine)
Abstract Objective This study investigates the impact of Titin (TTN) gene mutations on radiotherapy sensitivity in rectum adenocarcinoma (READ) by examining changes in the tumour immune microenvironment. Methods Data on gene expression and mutations in READ were obtained from The Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) databases. Bioinformatics analysis explored the correlation between TTN mutations and immune cell infiltration. In vitro, lentiviral vectors were used to assess TTN mutations' effects on ANKRD1 expression in two READ cell lines. ANKRD1 was overexpressed, and clonogenic assays evaluated radiotherapy sensitivity. Flow cytometry, immunofluorescence, and comet assays examined mutations' impact on cell cycle, apoptosis, and DNA damage response (DDR). An in vivo mouse model and formalin‐fixed paraffin‐embedded samples from locally advanced rectal cancer (LARC) patients before and after radiotherapy were analyzed, followed by prognostic evaluation. Results Bioinformatics revealed that TTN mutations increase radiation sensitivity in LARC by slowing cell proliferation, promoting apoptosis, and reducing DDR. TTN mutations also inhibit ANKRD1 expression via JUN disruption and enhance CD4/CD8 T‐cell infiltration, improving anti‐tumour immunity and outcomes. Observations from the clinical study showed a substantial decline in ANKRD1 expression levels alongside a notable surge in the counts of CD4+ and CD8+ T cells after undergoing radiotherapy. Patients with TTN mutations, low ANKRD1 expression, and high densities of CD4+ and CD8+ T cells had longer 3‐year disease‐free survival in READ. Conclusion Our findings reveal that TTN mutations can serve as biomarkers for enhanced radiotherapy sensitivity in READ. By altering the tumour's immune microenvironment, these mutations may provide a novel target for personalized radiotherapy strategies, potentially improving therapeutic outcomes in patients with READ. Highlights The association between TTN mutations and tumour mutation burden, as well as immune cell infiltration in READ, is examined. TTN mutations enhance the radiation sensitivity of READ cells and weaken DNA damage repair in response to radiation. TTN mutations increase the radiation sensitivity of READ cells by inhibiting ANKRD1. The infiltration of CD8+ and CD4+ T cells induced by TTN mutations is essential for anti‐tumour immunity. TTN mutations serve as a biomarker for the pathological response to preoperative radiotherapy in READ.